Association of genetic variants of PD1 with recurrent pregnancy loss. (23rd March 2018) - Hayashi, Yuko; Nishiyama, Takeshi; Nakatochi, Masahiro; Suzuki, Shugo; Takahashi, Satoru; Sugiura‐Ogasawara, Mayumi
Abstract: Purpose: Programmed cell death 1 (PD1) and PD ligand 1 (PDL1) are speculated to have an important role in maintaining a normal pregnancy and there are also a few reports of an association between the single‐nucleotide polymorphisms (SNPs) of PD1 or PDL1 and diseases in humans. The association was examined between the polymorphisms of PD1, PDL1, CTLA4 and recurrent pregnancy loss (RPL). Methods: The study group consisted of 243 women with two or more pregnancy losses and 176 parous women. The frequency of three SNPs of PD1, two of PDL1, and four of CTLA4 were compared between the patients and controls. Next, the subsequent live birth rates in the patients with RPL with and without risk alleles were examined. Results: Two SNPs (rs36084323 and rs3481962) of PD1 were found to occur at significantly higher frequencies in the patient group than in the control group. The subsequent live birth rate of the patients with vs. without the risk alleles of rs36084323 and rs3481962 were 83.3% vs. 83.3% and 81.6% vs. 84.0%, respectively. Conclusion: Variations of the PD1 gene were identified as risk factors for RPL. However, the presence or absence of the PD1 risk alleles had no predictive effect on the subsequent pregnancy outcome. Abstract : Variations of the PD1 gene were confirmed to be risk factors for RPL. However, no predictive effect of the PD1 risk allele on subsequent pregnancy outcome have been identified.